2021
DOI: 10.3389/fmicb.2021.637813
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Invasive Streptococcus pneumoniae Serotype 24F in Lebanon: Complete Genome Sequencing Reveals High Virulence and Antimicrobial Resistance Characteristics

Abstract: BackgroundInvasive pneumococcal disease (IPD) remains a global health problem. IPD incidence has significantly decreased by the use of pneumococcal conjugate vaccines (PCV). Nevertheless, non-PCV serotypes remain a matter of concern. Eight Streptococcus pneumoniae serotype 24F isolates, belonging to a non-PCV serotype, were detected through the Lebanese Inter-Hospital Pneumococcal Surveillance Program. The aim of the study is to characterize phenotypic and genomic features of the 24F isolates in Lebanon.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
(53 reference statements)
1
7
0
Order By: Relevance
“… 7 Unlike GPSC10, GPSC6 was susceptible to penicillin and erythromycin. This observation coincided with the lower consumption of penicillin and macrolides (a class of antibiotic that includes erythromycin) in Denmark, as compared with other countries such as France, 2 , 3 Lebanon, 12 and Spain 14 , 15 where the increase in serotype 24F was mediated by the multidrug-resistant GPSC10 ( appendix 1 p 23 ) lineage. According to ResistanceMap , France, Lebanon, and Spain consumed 1·8–2·2 times more penicillin and 1·2–2·0 times more macrolides than Denmark in 2015.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“… 7 Unlike GPSC10, GPSC6 was susceptible to penicillin and erythromycin. This observation coincided with the lower consumption of penicillin and macrolides (a class of antibiotic that includes erythromycin) in Denmark, as compared with other countries such as France, 2 , 3 Lebanon, 12 and Spain 14 , 15 where the increase in serotype 24F was mediated by the multidrug-resistant GPSC10 ( appendix 1 p 23 ) lineage. According to ResistanceMap , France, Lebanon, and Spain consumed 1·8–2·2 times more penicillin and 1·2–2·0 times more macrolides than Denmark in 2015.…”
Section: Discussionmentioning
confidence: 72%
“… 4 In France, a big increase in pneumococcal meningitis cases occurred 5 years after the roll out of PCV13, mainly driven by serotype 24F. 2 , 3 This serotype also mediated serotype replacement in multiple other countries, such as Argentina, 5 Canada, 6 Denmark, 7 Germany, 8 Israel, 9 Italy, 10 Japan, 11 Lebanon, 12 Norway, 13 Spain, 14 , 15 and the UK, 16 and was reported to be the predominant serotype causing invasive pneumococcal disease (IPD) in Portugal 17 after PCV13 introduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumococcus is a commensal bacterium that normally colonizes the human nasopharyngeal cavity and is transmitted by droplets and aerosols either from infected patients or healthy carriers [45]. Although this species is rarely reported in mastitis, various epidemiological studies showed its high prevalence in the Lebanese community [46,47]. This allows us to speculate that there is a potential threat of contamination by handlers.…”
Section: Discussionmentioning
confidence: 99%
“…The NVT 24F has been reported to be an emerging serotype among patients with IPD (mostly [87.5%] <6 years of age with unknown pneumococcal vaccination status) in Lebanon, with 4 cases noted in 2019. 95 The genome sequencing of this serotype, isolated from samples collected between 2013 and 2019, showed that it is highly virulent and antimicrobial resistant. 95 The prevalence of this NVT among IPD cases in children has also been reported in the European and Western Pacific regions.…”
Section: Lebanonmentioning
confidence: 99%